2019
DOI: 10.31703/gssr.2019(iv-iv).43
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners’ Perception about Professional Learning Practices at Higher Secondary Level in Public and Private Sector

Abstract: The study analyzed practitioners’ perceptions about professional learning practices at higher secondary level in public and private sector. The components of professional learning practices were teaching learning process, students’ development, teachers’ professional relationship and service, institutional development and personal and professional growth. The objectives of this paper focused on checking practitioners’ insights regarding above given components. The sample of the study were 633 practitioners. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The constitutive characteristics of the concept of identity (Casta ñeda, 2011) Teachers' professional identities (TPI) involve self-reflection on past practices and personal identities, guiding their present actions with an eye on students' future. Competent teachers establish connections between students' past, present, and future actions, positively influencing their knowledge (Tabassum & Malik, 2017). A well-developed and recognized professional identity enhances teachers' effectiveness, leading to students' betterment as contributing members of society.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The constitutive characteristics of the concept of identity (Casta ñeda, 2011) Teachers' professional identities (TPI) involve self-reflection on past practices and personal identities, guiding their present actions with an eye on students' future. Competent teachers establish connections between students' past, present, and future actions, positively influencing their knowledge (Tabassum & Malik, 2017). A well-developed and recognized professional identity enhances teachers' effectiveness, leading to students' betterment as contributing members of society.…”
Section: Figurementioning
confidence: 99%
“…Findings of the study conducted in Cyprus by Karousiou et al (2019) revealed that teachers' professional identities, along with supporting structures like loyalty to the profession and access to learning opportunities and resources, influenced their identities. Tabassum and Malik (2017) conducted a local study comparing the professional identities and learning methods of college teachers in public and private sectors, with 633 participants. Findings indicated that private college teachers were more motivated for professional growth compared to their public college counterparts.…”
Section: Figurementioning
confidence: 99%